Real Time Environment Simulation through Virtual Reality - Maheswari, R; Sheeba Rani Gnanamalar, S; Gomathy, V; Sharmila, B (International Journal of Engineering and Technology, 2018)
The primary objective of the work is to develop a simulation which changes its environment based on the outside environment. This is done by getting the input from the sensors and sending it to the cloud platform and then getting the sensor data into the simulation and changing the environment of it.The aim of the work is to design an embedded device which could collect sensor values of environment defining variables like pressure, temperature, altitude and amount of light and use it accordingly to change the environment of the simulation. This was achieved by constructing embedded device which relies on sensors to transmit the reading of environment defining factors to a cloud services provided by Thinkspeak platform. These reading are archived and can be accessed by the android application to change its environment.